Potassium-doped chain-shaped manganous-manganic oxide positive electrode material and preparation method and application thereof
By using potassium-doped chain-like manganese tetroxide cathode material K-Mn3O4-NCs@PANI composite material, the problems of poor conductivity and dissolution of manganese-based oxides in aqueous zinc-ion batteries have been solved, achieving high capacity and stable electrochemical performance, thus promoting its commercial application.
Patent Information
- Application Number
- CN202411268574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-11
AI Technical Summary
Existing manganese-based oxides in aqueous zinc-ion batteries suffer from poor conductivity, dissolution and volume expansion of Mn, and slow Zn2+ reaction kinetics, resulting in limited capacity decay and rate performance, which hinders their commercial application.
A potassium-doped chain-like manganese tetroxide cathode material, K-Mn3O4-NCs@PANI composite material, is used. By wrapping the K-doped manganese tetroxide nanochains with a polyaniline protective layer, a high aspect ratio conductive network is formed, which improves electronic conductivity and stability and inhibits the dissolution of Mn.
It significantly improves the electrochemical performance of zinc-ion batteries, exhibiting high specific capacity and good cycle stability. The discharge specific capacity reaches 510 mAh g-1 at a current density of 0.1 Ag-1, and still maintains 203 mAh g-1 at a current density of 5 Ag-1. After 20,000 cycles, the capacity remains at 90.3 mAh g-1.
Smart Images

Figure CN119297270A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and specifically relates to a potassium-doped chain manganese tetraoxide positive electrode material and a preparation method and application thereof. Background Art
[0002] With the development of science and technology, the research and development of efficient energy storage technology has attracted widespread attention. Compared with lithium-ion batteries, which are expensive and have safety issues, aqueous zinc-ion batteries (AZIBs) are expected to become a substitute for lithium-ion batteries due to their abundant resources, environmental friendliness, low cost and high safety. Cathode material is one of the important factors affecting the electrochemical performance of AZIBs. In recent years, many cathode materials have been developed, such as manganese-based oxides, vanadium-based oxides, polyanion compounds, quinone compounds and Prussian blue analogs. Manganese oxides have attracted widespread attention due to their abundant reserves, environmental friendliness, high discharge voltage and easy synthesis. However, the practical application of these oxides in AZIBs faces some challenges, such as dissolution problems during the cycle, volume expansion, Zn 2+ Slow reaction kinetics and inherently poor conductivity cause the capacity of aqueous zinc-ion batteries to decay significantly during cycling, seriously hindering their commercial development.
[0003] To overcome these obstacles and enable practical applications of Mn-based cathodes in AZIBs, researchers have explored a variety of research strategies, including morphology / structure design, protection layer construction, defect engineering, and ion / molecular pre-doping. The morphology / structure design strategy includes the development of porous / hollow / hierarchical cathode nano / microstructures with 2D and 3D structures. These nanostructures have large specific surface areas and high electrical conductivity, thereby increasing the contact area between the active material and the electrolyte. As a result, both the electronic conductivity and ion diffusion pathways are improved, facilitating the Zn 2+ The protective layer strategy aims to form a coating on the surface of the manganese-based cathode, such as carbon, conductive polymers, and a series of metal oxides, to prevent it from directly contacting the electrolyte, thereby reducing the Mn 2+ Dissolution. Cathode defect engineering aims to improve conductivity by adjusting the local electronic structure while improving the diffusion capacity of zinc ions by introducing unsaturated sites as active chemical adsorption sites. By introducing ions and molecules, ion / molecule pre-insertion can increase the interlayer spacing, thereby reducing the strong electrostatic interaction between highly polarized zinc ions and the Mn-O layer. This approach reduces the migration barrier of zinc ions and is considered a viable solution to improve the reaction kinetics.
[0004] However, these strategies inevitably bring some negative effects. The morphological / structural design of the cathode and the construction of the protective layer inevitably lead to a reduction in active materials. Defect engineering usually induces instability in the crystal structure, while ion / molecular pre-insertion often leads to blockage of ion channels. Although many studies have reported strategies to improve the electrochemical performance of manganese dioxide anodes, the theoretical capacity of manganese dioxide is still relatively low (250-308 mAh g -1 ). In recent years, low-valent manganese oxides, such as Mn3O4, Mn2O3 and MnO, have attracted widespread attention. Among them, due to its unique +2 and +3 mixed valence states, the theoretical capacity of Mn3O4 is higher than that of Mn 4+ / Mn 3+ AZIBs (~308 mAh g -1 ) High 468.56mAh g -1 , which is considered as a promising anode material. However, the inherent disadvantages of manganese oxides, such as volume expansion, poor electronic / ionic conductivity, sluggish zinc ion reaction kinetics, and dissolution issues, still need to be overcome in Mn3O4. These shortcomings often lead to rapid capacity decay and limited rate performance, hindering the practical application of Mn3O4 in AZIBs. In this work, we adopt a synthetic strategy that combines morphology / structure design, ion doping, and protective layer encapsulation to address these challenges. Summary of the invention
[0005] Technical issues solved:
[0006] The present invention aims at the deficiencies of the prior art and solves the problems of the poor conductivity of the current manganese-based metal oxides, the dissolution and volume expansion of Mn during the reaction, and the 2+ In order to solve technical problems such as slow reaction kinetics, a potassium-doped chain manganese tetraoxide positive electrode material and its preparation method and application are provided. The prepared zinc ion battery material can improve the conductivity of manganese-based materials, while suppressing the inherent dissolution problem of manganese-based materials, thereby improving the electrochemical performance of zinc ion batteries.
[0007] Technical solution:
[0008] To achieve the above objectives, this application is implemented through the following technical solutions:
[0009] A potassium-doped chain-like manganese tetraoxide positive electrode material, the positive electrode material is a K-Mn3O4-NCs@PANI composite material, the positive electrode material consists of a K-doped manganese tetraoxide nanochain and a polyaniline protective layer tightly wrapped outside the manganese tetraoxide nanochain, the K-doped manganese tetraoxide nanochain has a diameter of 10-30nm, and the polyaniline coating thickness is 5-10nm.
[0010] A method for preparing a potassium-doped chain-shaped manganese tetraoxide positive electrode material comprises the following steps:
[0011] Step 1: Prepare a mixed solution A of isopropanol and deionized water, and dissolve manganese acetate tetrahydrate, potassium chloride and nitrilotriacetic acid in the mixed solution under magnetic stirring at a mass ratio of manganese acetate tetrahydrate: potassium chloride: nitrilotriacetic acid = 8-9:1-2:1.5-3 to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12h; when the temperature of the reactor drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven after washing, and dry it to obtain K-Mn-NTA, i.e., a white powder K-Mn-NCs precursor;
[0012] Step 2: Grind the white powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it in an air environment for 4 hours. After cooling, K-Mn3O4-NCs powder can be obtained;
[0013] Step 3: Prepare a mixed solution C of concentrated hydrochloric acid and deionized water in a volume ratio of 1:40, and take the mixed solution C and place it evenly in two beakers, respectively denoted as A and B; add aniline dropwise into beaker A and ultrasonically treat it with an ultrasonic power of 180 W, and disperse the K-Mn3O4-NCs powder into the ultrasonically treated solution; add ammonium persulfate to beaker B and stir to dissolve it with a stirring speed of 800 rpm, then add the solution dropwise into beaker A and stir at 800 rpm for 4 hours. Finally, after centrifugation, ultrasonic washing and drying, K-Mn3O4-NCs@PANI was obtained.
[0014] Furthermore, in the first step, the volume ratio of isopropanol to deionized water is 1:4, the magnetic stirring speed is 800 rpm, and the amounts of isopropanol and deionized water are 10 mL and 40 mL respectively.
[0015] Furthermore, in the first step, the dosages of manganese acetate tetrahydrate, potassium chloride and nitrilotriacetic acid are 8 g, 1 g and 1.5 g respectively.
[0016] Furthermore, in the first step, the vacuum drying temperature is 60° C. and the vacuum time is 8 hours.
[0017] Furthermore, the calcination temperature in the second step is 400°C.
[0018] Furthermore, the amounts used in the third step are 1 ml and 40 ml respectively.
[0019] Furthermore, in the third step, the mass volume ratio of K-Mn3O4-NCs:aniline:ammonium persulfate is 0.4g:200μL:0.5g.
[0020] Furthermore, in the third step, the centrifuge speed is 6000 rpm, and the centrifugation is 15 minutes; the ultrasonic cleaning machine power is 180 W, the ultrasound is 10 minutes, the drying temperature is 60° C., and the drying time is 8 hours.
[0021] The present application also discloses the application of a potassium-doped chain-shaped manganese tetraoxide positive electrode material in an aqueous zinc ion battery. The potassium-doped chain-shaped manganese tetraoxide positive electrode material is the positive electrode of the aqueous zinc ion battery, a 2M zinc sulfate aqueous solution is used as an electrolyte, a glass fiber GF-D is used as a separator, a zinc sheet is used as a negative electrode, and a zinc ion battery is assembled into a zinc ion battery at room temperature using a CR2032 battery shell; the assembled battery is subjected to a long cycle test on a battery test cabinet Neware BTS 7.6.0.
[0022] Beneficial effects:
[0023] The present application provides a potassium-doped chain manganese tetraoxide positive electrode material and a preparation method and application thereof, which has the following beneficial effects compared with the prior art:
[0024] 1. The present invention obtains a zinc ion battery positive electrode material with a network structure by coating a PANI conductive protective layer on K-Mn3O4-NCs. The positive electrode material has a high aspect ratio, high conductivity and good stability;
[0025] 2. K in the present invention + Doping can adjust the local electronic structure of the Mn3O4 cathode, induce oxygen vacancies, improve the conductivity, and provide a catalyst for Zn 2+ The diffusion provides more active sites;
[0026] 3. The 1D K-Mn3O4-NCs in the present invention are composed of K-Mn3O4 nanoparticles and conductive carbon interconnected, thereby effectively reducing the contact resistance between particles and promoting the rapid transfer of electrons;
[0027] 4. The high aspect ratio of K-Mn3O4-NCs significantly increases the electrochemical reaction area and shortens the Zn 2+ The diffusion length of
[0028] 5. The polyaniline layer in the present invention is in-situ polymerized on K-Mn3O4-NCs, which can not only shield corrosion, but also connect 1DK-Mn3O4-NCs into a continuous conductive network, inhibit volume expansion, and improve stability;
[0029] 6. The positive electrode material of the present invention is used for the positive electrode of zinc ion battery at 0.1Ag -1 The specific capacity at the current density is as high as 510 mAh g -1 , at 5Ag -1 The current density reaches 203 mAh g -1 ;
[0030] 7. The zinc ion battery of the present invention has good cycle performance. -1 After 20,000 cycles at the same current density, the specific capacity remains at 90.3 mAh g -1 The average capacity decreases by 0.026‰ per circle. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope (SEM) image of K-Mn3O4-NCs@PANI obtained in Example 1 of the present invention;
[0032] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of K-Mn3O4-NCs@PANI obtained in Example 1 of the present invention;
[0033] Figure 3 Schematic diagram of the structure of K-Mn3O4-NCs@PANI obtained in Example 1 of the present invention;
[0034] Figure 4 This is a transmission electron microscope (TEM) image of K-Mn3O4-NCs@PANI obtained in Example 1 of the present invention;
[0035] Figure 5 The rate performance diagram of the zinc ion battery of Example 1 and Comparative Examples 1, 2, 3, and 4 provided by the present invention;
[0036] Figure 6 The zinc ion battery 5Ag of Example 1 and Comparative Examples 1, 2, 3, and 4 provided by the present invention -1 Specific capacity and cycling performance over 20,000 cycles at the same current density. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the principles and features of the present invention are comprehensively and carefully described below in conjunction with the accompanying drawings and preferred embodiments. The embodiments are only used to explain the present invention and are not intended to limit the scope of the present invention.
[0038] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0039] In order to further illustrate the present invention, the preparation method and application of the potassium-doped chain-shaped manganese-zinc tetroxide positive electrode material for polyaniline-coated ion batteries provided by the present invention are described in detail below in conjunction with the examples.
[0040] Embodiment 1:
[0041] A method for preparing a potassium-doped chain-shaped manganese tetraoxide positive electrode material comprises the following steps:
[0042] Step 1: Prepare a mixed solution A of 10 mL of isopropanol and 40 mL of deionized water, and dissolve 8 g of manganese acetate tetrahydrate, 1 g of potassium chloride and 1.5 g of nitrilotriacetic acid in the mixed solution under 800 rpm magnetic stirring to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12 h; when the temperature of the reactor drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, and after washing, transfer it to a vacuum drying oven and dry it at 60°C for 12 h to obtain K-Mn-NTA, i.e., white powder.
[0043] K-Mn-NCs precursor;
[0044] Step 2: Grind the white powder and place it on a quartz boat and place the quartz boat in a tube furnace. Then,
[0045] Calcinate at 400 °C for 4 hours and then cool to obtain K-Mn3O4-NCs powder;
[0046] Step 3: Prepare a mixed solution C with 1 mL of concentrated hydrochloric acid and 40 mL of deionized water, and take the mixed solution C and place it evenly in two beakers, which are marked as A and B respectively; add 200 μL of aniline dropwise into beaker A and treat it ultrasonically with an ultrasonic power of 180 W, and disperse the K-Mn3O4-NCs powder into the ultrasonically treated solution; add 0.5 g of ammonium persulfate to beaker B and stir at 800 rpm to dissolve, then add the solution dropwise into beaker A and stir at 800 rpm for 4 hours. Finally, after centrifugation, ultrasonic washing and drying at 60-75°C for 12 hours, the centrifuge speed is 6000 rpm and centrifugation is performed for 15 minutes; the ultrasonic cleaning machine power is 180 W and ultrasonication is performed for 10 minutes to obtain K-Mn3O4-NCs@PANI.
[0047] Figure 1 is a scanning electron microscope (SEM) image of K-Mn3O4-NCs@PANI obtained in Example 1. Figure 1 Due to the wrapping of polyaniline, the surface of K-Mn3O4-NCs@PANI becomes smoother and the diameter of these chain structures is about 30 nm. Figure 2 This is the high-resolution transmission electron microscopy (HRTEM) image of K-Mn3O4-NCs@PANI. Figure 2 It can be seen that the lattice spacing of the composite material is about 0.31nm. Figure 3This is a schematic diagram of the K-Mn3O4-NCs@PANI structure obtained in Example 1 of the present invention. It can be seen that the above materials eventually form a conductive network. The 1D K-Mn3O4-NCs are protected inside the PANI layer, and the K-Mn3O4k particles are linked to each other to form a stable one-dimensional chain structure. Figure 4 This is a transmission electron microscope (TEM) image of K-Mn3O4-NCs@PANI obtained in Example 1 of the present invention. It can be seen that the PANI protective layer is very comprehensively wrapped on the surface of the K-Mn3O4-NCs nanochain.
[0048] Application of potassium-doped chain manganese tetraoxide positive electrode material in aqueous zinc ion batteries:
[0049] Step 1, preparation of slurry: K-Mn3O4-NCs@PANI, conductive carbon black and binder (PVDF) are fully ground and stirred in a ratio of 8:1:1, and mixed evenly to form a slurry;
[0050] Step 2: Use a mold to evenly coat the slurry on the titanium foil, and then transfer the titanium foil to a vacuum drying oven and dry it at 50°C for 10 hours;
[0051] Step 3, preparation of electrode sheet: cut the dried titanium foil into small discs with a diameter of 16 mm, which are the positive electrode sheets;
[0052] Step 4: Use the prepared circular electrode as the positive electrode and the glass fiber filter membrane as the diaphragm. -1 ZnSO4 solution was used as electrolyte, zinc sheet was used as negative electrode, and button-type CR2032 symmetrical battery was assembled in the order of negative electrode shell, spring sheet, gasket, negative electrode sheet, diaphragm, positive electrode sheet and positive electrode shell. The electrochemical performance was tested after standing for 12 hours.
[0053] Embodiment 2:
[0054] A method for preparing a potassium-doped chain-shaped manganese tetraoxide positive electrode material comprises the following steps:
[0055] Step 1: Prepare a mixed solution A of 10 mL of isopropanol and 40 mL of deionized water, and dissolve 6 g of manganese acetate tetrahydrate, 0.8 g of potassium chloride and 1 g of nitrilotriacetic acid in the mixed solution under magnetic stirring at 800 rpm to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12 h; when the temperature of the reactor drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven after washing, and dry it at 60°C for 12 h to obtain K-Mn-NTA, i.e., a white powder K-Mn-NCs precursor;
[0056] Step 2: Grind the white powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it at 350°C for 4 hours in an air environment. After cooling, K-Mn3O4-NCs powder can be obtained.
[0057] Step 3: Prepare a mixed solution C with 1 ml of concentrated hydrochloric acid and 40 ml of deionized water, and take the mixed solution C and place it evenly in two beakers, respectively labeled A and B; add 150 μL of aniline dropwise into beaker A and ultrasonically treat it with an ultrasonic power of 180 W, and disperse the K-Mn3O4-NCs powder into the ultrasonically treated solution; add 0.4 g of ammonium persulfate to beaker B and stir to dissolve it with a stirring speed of 800 rpm, then add the solution dropwise into beaker A, and finally stir at 800 rpm for 4 hours, and finally centrifuge, ultrasonically wash and dry at 60-75°C for 12 hours, centrifuge at 6000 rpm, 15 min; ultrasonic cleaner at 180 W, 10 min, to obtain K-Mn3O4-NCs@PANI.
[0058] Comparative Example 1
[0059] A method for preparing a positive electrode material comprises the following steps:
[0060] Step 1: Prepare a mixed solution A of 10 mL of isopropanol and 40 mL of deionized water, and dissolve 8 g of manganese acetate tetrahydrate, 1 g of potassium chloride and 1.5 g of nitrilotriacetic acid in the mixed solution under magnetic stirring at 800 rpm to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12 h; when the reactor temperature drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven, and dry it at 60°C for 12 h to obtain K-Mn-NTA, i.e., a white powder K-Mn-NCs precursor;
[0061] Step 2: Grind the white powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it at 400°C for 4 hours in an air environment. After cooling, K-Mn3O4-NCs powder can be obtained.
[0062] Step 3: Preparation of slurry: K-Mn3O4-NCs, conductive carbon black and binder (PVDF) were fully ground and stirred in a ratio of 8:1:1, and mixed evenly to form a slurry;
[0063] Step 2: Use a mold to evenly coat the slurry on the titanium foil, and then transfer the titanium foil to a vacuum drying oven and dry it at 50°C for 10 hours;
[0064] Step 3, preparation of electrode sheet: cut the dried titanium foil into small discs with a diameter of 16 mm, which are the positive electrode sheets;
[0065] Step 4: Use the prepared circular electrode as the positive electrode and the glass fiber filter membrane as the diaphragm. -1 ZnSO4 solution was used as electrolyte, zinc sheet was used as negative electrode, and button-type CR2032 symmetrical battery was assembled in the order of negative electrode shell, spring sheet, gasket, negative electrode sheet, diaphragm, positive electrode sheet and positive electrode shell. The electrochemical performance was tested after standing for 12 hours.
[0066] Comparative Example 2:
[0067] A method for preparing a positive electrode material comprises the following steps:
[0068] Step 1: Prepare a mixed solution A of 10 mL of isopropanol and 40 mL of deionized water, and dissolve 8 g of manganese acetate tetrahydrate and 1.5 g of nitrilotriacetic acid in the mixed solution under magnetic stirring at 800 rpm to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12 h; when the temperature of the reactor drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven, and dry it at 60°C for 12 h to obtain Mn-NTA, i.e., a white powder Mn-NCs precursor;
[0069] Step 2: Grind the white powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it at 400°C for 4 hours in an air environment. After cooling, Mn3O4-NCs powder can be obtained.
[0070] Step 3: Preparation of slurry: Mn3O4-NCs, conductive carbon black and binder (PVDF) were fully ground and stirred in a ratio of 8:1:1, and mixed evenly to form slurry;
[0071] Step 2: Use a mold to evenly coat the slurry on the titanium foil, and then transfer the titanium foil to a vacuum drying oven and dry it at 50°C for 10 hours;
[0072] Step 3, preparation of electrode sheet: cut the dried titanium foil into small discs with a diameter of 16 mm, which are the positive electrode sheets;
[0073] Step 4: Use the prepared circular electrode as the positive electrode and the glass fiber filter membrane as the diaphragm. -1 ZnSO4 solution was used as electrolyte, zinc sheet was used as negative electrode, and button-type CR2032 symmetrical battery was assembled in the order of negative electrode shell, spring sheet, gasket, negative electrode sheet, diaphragm, positive electrode sheet and positive electrode shell. The electrochemical performance was tested after standing for 12 hours.
[0074] Comparative Example 3:
[0075] A method for preparing a positive electrode material comprises the following steps:
[0076] Step 1: Prepare a mixed solution A of 10 mL of isopropanol and 40 mL of deionized water, dissolve 8 g of manganese acetate tetrahydrate into the mixed solution under magnetic stirring at 800 rpm to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat at 180 °C.
[0077] Heating for 12 hours; when the temperature of the reactor drops to room temperature, the pink precipitate is washed three times with deionized water and anhydrous ethanol, transferred to a vacuum drying oven, and dried at 60°C for 12 hours to obtain a Mn salt, i.e., a Mn precursor;
[0078] Step 2: Grind the Mn precursor powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it at 400°C for 4 hours in an air environment, and then obtain Mn3O4 after cooling;
[0079] Step 3: Preparation of slurry: Mn3O4, conductive carbon black and binder (PVDF) are fully ground and stirred in a ratio of 8:1:1, and mixed evenly to form slurry;
[0080] Step 2: Use a mold to evenly coat the slurry on the titanium foil, and then transfer the titanium foil to a vacuum drying oven and dry it at 50°C for 10 hours;
[0081] Step 3: Preparation of electrode sheet: Cut the dried titanium foil into small discs with a diameter of 16 mm, which are the positive electrode sheets;
[0082] Step 4: Use the prepared circular electrode as the positive electrode and the glass fiber filter membrane as the diaphragm. -1 ZnSO4 solution was used as electrolyte, zinc sheet was used as negative electrode, and button-type CR2032 symmetrical battery was assembled in the order of negative electrode shell, spring sheet, gasket, negative electrode sheet, diaphragm, positive electrode sheet and positive electrode shell. The electrochemical performance was tested after standing for 12 hours.
[0083] Test Case
[0084] The zinc ion batteries obtained in Example 1 and Comparative Examples 1, 2, and 3 were subjected to constant current charge and discharge, cycle performance test, and rate performance test using a charge and discharge instrument from Shenzhen Xinwei Co., Ltd. The test temperature herein was an ambient temperature of 26° C., and the charge and discharge voltage cutoff range was 0.8 to 1.8 V. The test results are shown in FIG. Figure 5 and Figure 6 shown.
[0085] Figure 5 The figure is a rate performance diagram of the zinc ion battery obtained in Example 1 and Comparative Examples 1, 2, and 3 provided by the present invention. The discharge capacity of the zinc ion battery assembled with K-Mn3O4-NCs@PANI as the positive electrode material provided in Example 1 is from 0.1A to -1 501.5mAh g -1To 5Ag -1 The discharge capacity after that is 203.2 mAh g -1 , the capacity retention rate is 40.5%. When the current density rises back to 5A -1 When -1 , with extremely strong reversibility. However, the specific capacity of comparative examples 1, 2, and 3 at each current density is significantly lower than that of zinc ion batteries with K-Mn3O4-NCs@PANI as the positive electrode. Figure 6 The long cycle performance diagram of the zinc ion battery obtained in Example 1 and Comparative Examples 1, 2, and 3 provided by the present invention. Figure 6 It can be seen that the zinc ion battery assembled with K-Mn3O4-NCs@PANI as the positive electrode material provided in Example 1 has a high -1 Long cycle performance at current density with an initial capacity of 190.0 mAh g -1 After 20,000 cycles, it still maintains 90.3 mAh g -1 The specific capacity of the zinc ion battery with materials in comparative examples 1, 2, and 3 as electrodes is 0.026‰, and the capacity decays rapidly, the discharge specific capacity and stability are relatively poor, and the dissolution of manganese is serious. The zinc ion battery with K-Mn3O4-NCs@PANI material as electrode has excellent rate performance and high stability, showing excellent electrochemical properties, and has good initial specific capacity, cycle performance, and rate performance.
[0086] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A potassium-doped chain-like manganese tetraoxide positive electrode material, wherein the positive electrode material is a K-Mn3O4-NCs@PANI composite material, and the positive electrode material is composed of a K-doped manganese tetraoxide nanochain and a polyaniline protective layer tightly wrapped outside the manganese tetraoxide nanochain, wherein the diameter of the K-doped manganese tetraoxide nanochain is 10-30nm, and the polyaniline coating thickness is 5-10nm.
2. A method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 1, characterized in that: The specific steps include: Step 1: Prepare a mixed solution A of isopropanol and deionized water, and dissolve manganese acetate tetrahydrate, potassium chloride and nitrilotriacetic acid in the mixed solution under magnetic stirring at a mass ratio of manganese acetate tetrahydrate: potassium chloride: nitrilotriacetic acid = 8-9:1-2:1.5-3 to obtain a mixed solution B; then transfer the mixed solution B to a reactor and heat it at 180°C for 12h; when the temperature of the reactor drops to room temperature, wash the pink precipitate three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven after washing, and dry it to obtain K-Mn-NTA, i.e., a white powder K-Mn-NCs precursor; Step 2: Grind the white powder and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it in an air environment for 4 hours. After cooling, K-Mn3O4-NCs powder can be obtained; Step 3: Prepare a mixed solution C of concentrated hydrochloric acid and deionized water in a volume ratio of 1:40, and take the mixed solution C and place it evenly in two beakers, respectively denoted as A and B; add aniline dropwise into beaker A and ultrasonically treat it with an ultrasonic power of 180 W, and disperse the K-Mn3O4-NCs powder into the ultrasonically treated solution; add ammonium persulfate to beaker B and stir to dissolve it with a stirring speed of 800 rpm, then add the solution dropwise into beaker A and stir at 800 rpm for 4 hours. Finally, after centrifugation, ultrasonic washing and drying, K-Mn3O4-NCs@PANI was obtained.
3. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: In the first step, the volume ratio of isopropanol to deionized water is 1:4, the magnetic stirring speed is 800 rpm, and the amounts of isopropanol and deionized water are 10 mL and 40 mL respectively.
4. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: In the first step, the dosages of manganese acetate tetrahydrate, potassium chloride and nitrilotriacetic acid are 8 g, 1 g and 1.5 g respectively.
5. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: The vacuum drying temperature in the first step is 60° C. and the vacuum time is 8 h.
6. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: The calcination temperature in the second step is 400°C.
7. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: In the third step, the amounts of concentrated hydrochloric acid and deionized water used are 1 ml and 40 ml respectively.
8. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: In the third step, the mass volume ratio of K-Mn3O4-NCs:aniline:ammonium persulfate is 0.4g:200μL:0.5g.
9. The method for preparing the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 2, characterized in that: In the third step, the centrifuge speed is 6000 rpm, and the centrifugation is 15 minutes; the ultrasonic cleaning machine power is 180 W, the ultrasonic cleaning is 10 minutes, the drying temperature is 60° C., and the drying time is 8 hours.
10. An application of the potassium-doped chain-shaped manganese tetraoxide positive electrode material according to claim 1 in an aqueous zinc ion battery, characterized in that: The potassium-doped chain manganese tetraoxide positive electrode material is the positive electrode of the aqueous zinc ion battery, a 2M zinc sulfate aqueous solution is used as the electrolyte, a glass fiber GF-D is used as the separator, a zinc sheet is used as the negative electrode, and a zinc ion battery is assembled at room temperature using a CR2032 battery shell; the assembled battery is subjected to a long cycle test on a battery test cabinet Neware BTS 7.6.0.
Citation Information
Patent Citations
Manganous-manganic oxide / carbon nanotube composite material as well as preparation method and application thereof
CN110911653A
K-doped alpha-manganese dioxide nanorod, direct writing forming ink, zinc ion battery positive electrode and preparation methods of K-doped alpha-manganese dioxide nanorod, direct writing forming ink and zinc ion battery positive electrode
CN115000395A
Preparation method of homogeneous manganese dioxide / polyaniline zinc ion battery positive electrode material
CN117012946A
Aqueous sodium-ion battery negative electrode material, preparation method thereof and aqueous sodium-ion battery
CN117117163A
battery
JP1990220373A
Cited By
High-specific-surface-area manganous-manganic-oxide microsphere electrode material and preparation method thereof
CN121202194A
A high specific surface area trimanganese tetraoxide microsphere electrode material and a preparation method thereof
CN121202194B